Characterisation of bacteriophages for controlling bacterial blight disease in rice - Jonit, Nur Qamariah (2017)
Rice cultivation is the principle activity and source of income for millions of household around the globe and several countries in Asia and Africa. Over 90 percent of the world’s rice is produced and consumed in the Asia-Pacific Region. Bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae (Xoo) is the most serious disease of rice in South-East Asia. There are many approaches in order to combat the disease. Chemical application and antibiotics are among the most famous and easy method used to suppress the disease. However, the long-term usage may render harmful side effects to the ecosystems and may lead to the emergence of resistant-bacteria strains. Thus, the present study was carried out with the aim to isolate bacteriophages from various sources for controlling local Xoo in rice. The second aim would be to isolate and identify Xoo from infected rice plant which served as a host for isolation of potential phages. The bacteriophage isolates were analysed based on their lytic activity towards Xoo, host range, electron microscopy and their genomes were isolated to study their type, size and restriction enzyme profile patterns. The structural proteins of the phages were also studied by SDS-PAGE. Subsequently, the efficacy of a selected phage to reduce the incidence of BLB which Xoo as a host bacteria load in glass house was evaluated. Six lytic bacteriophages namely Qɸ-146, Qɸ-156, Qɸ-158, Qɸ-160, Qɸ-161 and Qɸ-162 were isolated from infected rice soil samples. Phage Qɸ-161 was found to demonstrate a broader host range in which it was able to infect Xanthomonas campestris, Ralstonia solanacearum, Bacillus methylotropicus and Bacillus siamensis apart from Xoo (the original host). The morphology of these phages indicated that they belonged to the Podoviridae family. All six phages revealed similar protein profile when analysed using SDS-PAGE with three major bands of proteins which had molecular weight of 100, 36 and 15 kDA. All phages had genome size of approximately 23 kb and differentiated by their EcoRI, BamHI dan HindIII restriction fragment patterns. Based on the overall characteristics of the phage isolates, all six phage isolates were then mixed to form phage cocktails for subsequent glass house study. With approximate 108 pfu/ml titer application of phage cocktails in rice challenged with approximate 108 cfu/ml of Xoo, it was found to reduce the incidence of BLB in rice. Untreated rice plant, exhibited severe infection symptoms on the leaves with a disease severity rate of 46.67% compared to treated plant, T1 with 23.61% on 42-day post-treatment. In conclusion, phages demonstrated potential as an alternative control method to increase the control efficacy of BLB and reduce the use of agrochemicals. However, further characterisation on phage-host interaction such as the effects of different pH, temperature and multiplicity of infection (MOI) ratio should be carried out. Further optimisation of both dosage and alternative routes of phage administration should also be carried out to enhance the efficacy of the phage.